Hjälptyglars inverkan på hästen - Zakrisson, Linnea (SLU/Dept. of Animal Environment and Health (until 231231), 2014)
The horse has been domesticated for several thousand years. It has gone from being used primarily for food and transportation, to become one of the most popular pets in Sweden. With over 150,000 practitioners, horseback riding is one of the biggest sports in Sweden and there is a variety of specializations to choose from. One orientation is western riding which is a broad sport with several disciplines where most originate in cattle work and other ranch tasks. Western riding is a growing sport in Sweden with an increasing number of practitioners and with many different organizations and associations, it is important that the correct knowledge of the equipment used is disseminated.